Method for making electroless metal / sulfur cathode, cathode made by the method, and battery using the cathode
By using non -electroplating metal/sulfur nanoma composite materials to prepare the cathode of lithium sulfur batteries, the problem of cathode low sulfur content and electrolytes in existing technologies is solved, and high energy density and cycle stability are achieved, promoting lithium sulfur sulfur Commercial development of batteries.
Patent Information
- Application Number
- CN202110493602.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-12
- Filing Date
- 2021-05-07
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-05-07
AI Technical Summary
In the production of electrodes, existing lithium-sulfur batteries require conductive carbon and polymer binder, resulting in low sulfur content of the cathode, high resistance, and excessive electrolyte use, limiting the high energy density and cycle stability of the battery.
采用非电镀金属/硫纳米复合材料,通过敏化、活化和酸性化学镀覆步骤,制备高金属含量和高硫含量的纳米复合材料,用于制备非电镀金属/硫阴极,减少对导电碳和 Dependence of adhesive.
Increased the activated material content of sulfur cathode, reduced the cathode resistance, reduced the amount of electrolyte, realized the high -ratio capacity, energy density, and cycle stability, and promoted the commercial application of lithium sulfur batteries.
Smart Images

Figure CN115084492B_ABST
Abstract
Description
[Technical field]
[0001] The invention relates to a method for preparing a non-electroplating metal / sulfur nanocomposite material, a non-electroplating metal / sulfur cathode using the nanocomposite material, and a battery using the cathode. [Background technology]
[0002] The low-cost and highly abundant sulfur element has the highest theoretical capacity in solid electrodes, and is therefore the most anticipated high-capacity cathode material for next-generation lithium batteries. In addition to the high theoretical energy density of lithium-sulfur batteries (up to 2,500Wh / kg), which is several times higher than that of lithium-ion batteries, the high-capacity sulfur cathode is not only cheap but also easy to obtain, and has now become the new favorite of academia and the energy industry.
[0003] In the field of energy conversion and storage, metal electrodes with electrocatalytic activity help improve reaction kinetics and stability. Therefore, metals are also used in sulfur cathodes to improve the chemical properties of batteries. However, the development of lithium-sulfur battery systems today still has the following problems that need to be explored and solutions proposed:
[0004] 《Sulfur-containing composite materials need to add conductive carbon and polymer binders when making electrodes》:
[0005] First, the high-capacity sulfur cathode is an insulating active material. In order to solve the low electrode conductivity of the sulfur cathode, the existing technology is mostly synthesized into sulfur-containing composite materials, most of which are carbon-sulfur composite materials as the research and development subject, and some are polymer sulfur composite materials. Carbon-sulfur composite materials use the high conductivity and porosity of carbon materials to improve the charge and stability of the sulfur cathode, and polymer sulfur composite materials use the adsorption of polymers to sulfur to improve the electrochemical stability of the electrode. However, all kinds of sulfur-containing composite materials need to be mixed with additional conductive carbon and polymer binders to make cathodes (refer to [Patent Document 1], [Patent Document 2]). Among them, the addition of additional conductive carbon is to improve the conductivity of the cathode, and the addition of binders belonging to inactive substances is to make the active substance and conductive carbon uniformly mixed and connected. According to [Non-Patent Document 1] to [Non-Patent Document 3], the disadvantages of adding binders when making cathodes include increasing cathode resistance, reducing the content of active substances, and requiring the use of carcinogenic / mutagenic and reproductively toxic N-methylpyrrolidone.
[0006] Limits on low sulfur content in cathodes:
[0007] The first factor to achieve high energy density batteries is to increase the content of active material (sulfur) in the cathode. However, due to the high insulation of sulfur and the need to add conductive carbon and binder (see [Non-Patent Document 1], [Non-Patent Document 2]), lithium-sulfur batteries are currently limited to low sulfur content (only 30-60wt%). In this case, it is difficult to achieve the high energy density advantage of the sulfur cathode, and it is inferior to showing the real electrochemical reaction characteristics of the sulfur cathode, resulting in erroneous research results and delaying the commercial application of the technology.
[0008] 《High sulfur loading cathode is not easy to make》:
[0009] Due to the high insulation property of sulfur, if the sulfur loading is increased from the usual low sulfur loading of 2.0 mg / cm 2 , increased to more than 5mg / cm 2 When the sulfur load is high, the sulfur cathode with high load will have a large amount of insulating sulfur substances, which will increase the resistance of the cathode and destroy the reaction kinetics. In addition, the high sulfur load cathode has a large amount of polysulfides participating in the battery reaction, which will further destroy the stability of the battery. Therefore, most battery research stops at high sulfur load cathodes, leaving a huge bottleneck between academic research and actual commercial use.
[0010] 《High electrolyte to sulfur weight ratio》:
[0011] According to [Non-Patent Document 1] to [Non-Patent Document 3], liquid polysulfides are produced when the sulfur cathode reacts in the battery discharge reaction, and the liquid polysulfides are soluble in the liquid electrolyte. Liquid polysulfides dissolved in the liquid electrolyte will increase the viscosity of the liquid electrolyte and reduce its ion conductivity; liquid polysulfides dissolved in the liquid electrolyte are easily lost from the sulfur cathode, causing irreversible power loss of the sulfur cathode; liquid polysulfides dissolved in the liquid electrolyte will further diffuse freely in the battery, and will diffuse to the lithium anode and corrode the lithium anode, causing instability between the electrode and the liquid electrolyte, resulting in unstable coulombic efficiency and poor cycle reversibility. The prior art uses a large amount of electrolyte (the electrolyte volume to sulfur weight ratio exceeds 20μL / mg) to ensure the reaction stability of the lithium-sulfur battery and maintain high coulombic efficiency. Furthermore, the electrodes of the prior art also rely on the porous skeleton formed by the conductive carbon and the conductive polymer to adsorb sulfur by adding conductive carbon and a binder during production. However, this method will cause the porous skeleton formed by the conductive carbon and the conductive polymer to absorb a large amount of electrolyte, and the conductive carbon and the binder will also absorb part of the electrolyte, so a very large amount of electrolyte is required. However, too much electrolyte will make the battery inferior to the actual electrochemical reaction characteristics of the sulfur cathode, and it will make it difficult for the sulfur cathode to achieve the advantage of high energy density, resulting in the lithium-sulfur battery being unable to be quickly put on the market.
[0012] 《Limited Development of Metal / Sulfur Composite Materials for Electrodes》:
[0013] Although metals have good conductivity, adsorption of polysulfides, and catalytic properties towards sulfur, they should be the most excellent materials for making composite materials. However, due to the high weight of metals relative to sulfur, the addition of metals may reduce the sulfur content in the cathode, and due to the defects of the known processes, metal / sulfur composite materials have not yet been effectively developed.
[0014] [Prior art literature]
[0015] [Patent Literature]
[0016] [Patent Document 1] CN103035879A
[0017] [Patent Document 2] CN108063257A
[0018]
Non-patent literature
[0019] [Non-patent document 1] More reliable lithium-sulfur batteries: status, solutions and prospects (DOI: 10.1002 / adma.201606823)
[0020]
Non-patent document 2
[0021] [Non-patent document 3] A Review of Functional Binders in Lithium–Sulfur Batteries (DOI: 10.1002 / aenm.201802107) [Summary of the invention]
[0022] [Technical problem to be solved by the invention]
[0023] The existing lithium-sulfur batteries have problems such as the need to add conductive carbon and polymer binders to the sulfur-containing composite materials when making electrodes, the limitation of low sulfur content in the cathode, the difficulty in making high-sulfur-loaded cathodes, the high electrolyte to sulfur weight ratio, and the limited development of metal / sulfur composite materials used in electrodes, which limit their electrochemical performance.
[0024]
Technical means
[0025] In view of this, the inventors have repeatedly conducted in-depth research to solve the above-mentioned problems, and provide a method for preparing an electroless metal / sulfur nanocomposite material, an electroless metal / sulfur cathode using the nanocomposite material, and a battery using the cathode, thereby completing the present invention.
[0026] That is, the present invention relates to a method for preparing a non-electroplating metal / sulfur nanocomposite material, the synthesis steps of which include:
[0027] A. Sensitization step: adding stannous chloride to hydrochloric acid to prepare a sensitizing solution, adding sulfur powder to the sensitizing solution, stirring evenly, and filtering to obtain a sensitizing powder;
[0028] B. Activation step: adding palladium chloride to hydrochloric acid to prepare an activation solution, adding the sensitized powder to the activation solution, stirring evenly, and filtering to obtain a pretreated powder;
[0029] C. Acidic chemical plating step: dissolving sodium acetate and metal salts in deionized water to prepare solution 1 containing metal ions; dissolving sodium hypophosphite in deionized water to prepare solution 2;
[0030] The solution 1 and the solution 2 are preheated to the same temperature and then mixed, and the pretreated powder is added and stirred evenly. After the metal ions are reduced to metal atoms, the obtained mixture is filtered, dried, and ground to prepare a non-electroplated metal / sulfur nanocomposite material.
[0031] The metal salt may be at least one selected from the group consisting of gold chloride, silver chloride, copper chloride, tin chloride, nickel chloride, cobalt chloride, and ferric chloride. In some embodiments, the hydrochloric acid used in the sensitization step and the activation step is an aqueous hydrochloric acid solution.
[0032] The stirring time of the sensitization step can be 10 to 180 minutes, preferably 60 minutes; the stirring time of the activation step can be 10 to 180 minutes, preferably 60 minutes; the stirring time of the acid chemical plating step can be 10 to 180 minutes, preferably 60 minutes.
[0033] Wherein, the same temperature may be 70-90°C.
[0034] Wherein, the sulfur content of the electroless metal / sulfur nanocomposite material may be 60-95wt%.
[0035] Wherein, the metal content of the electroless metal / sulfur nanocomposite material may be 5-40wt%.
[0036] In another aspect, the present invention relates to an electroless metal / sulfur cathode, which is made by a drop coating method, and the manufacturing steps include:
[0037] The electroless metal / sulfur nanocomposite material prepared by the above-mentioned preparation method is dissolved in an electrolyte, and then drop-coated on a current collector to form an electroless metal / sulfur cathode.
[0038] Wherein, the weight ratio of the electrolyte to sulfur may be 7 to 20 μL / mg.
[0039] Among them, its sulfur loading can be 2 to 14 mg / cm 2 (sulfur weight / electrode area).
[0040] In yet another aspect, the present invention relates to a battery made using the electroless metal / sulfur cathode as described above.
[0041] [Effects of the Invention]
[0042] In the method for preparing the electroless metal / sulfur nanocomposite material of the present invention, the stirring time of the sensitization step is 10 to 180 minutes, and the stirring time of the activation step is 10 to 180 minutes. By extending the sensitization and activation time, uniform pretreatment of the self-oxidation-reduction reaction sites on the surface of the sulfur powder can be performed, which is conducive to the formation of a homogeneous surface coating. Therefore, the electroless metal / sulfur nanocomposite material of the present invention can reach a high metal content of 5 to 40wt%.
[0043] In the method for preparing the non-electroplated metal / sulfur nanocomposite material of the present invention, acid chemical plating at a high temperature of 70 to 90° C. for 10 to 180 minutes (optimally 60 minutes) is used, which helps to reduce the generation of alloy impurities to only 1 to 5.5wt% or less. Therefore, the present invention can achieve high metal content and high sulfur content.
[0044] The metal content of the electroless metal / sulfur nanocomposite material plated by the present invention can be increased by controlling the concentration and temperature of the metal salt solution.
[0045] The electroless metal / sulfur nanocomposite material of the present invention can effectively improve the insulation of the sulfur cathode and greatly increase the active material content (sulfur content) of the cathode to 60-95wt%, achieving a high sulfur content. In this way, in addition to achieving high specific capacity and excellent energy density, the battery cycle stability can also be improved, making the battery using this cathode commercially viable.
[0046] The non-electroplated metal / sulfur nanocomposite material of the present invention can achieve high metal content. The conductive metal shell can improve the conductivity of the sulfur cathode to promote its reaction ability and improve the electrochemical reactivity of the cathode. The material has strong polysulfide adsorption and electrochemical catalysis. In addition to effectively reducing the amount of electrolyte, it can also achieve a cathode with a high sulfur load, so that the cathode exhibits excellent electrochemical utilization and electrochemical reversibility. The material can also enable the battery to complete a stable long cycle at different high and low rates.
[0047] The electroless metal / sulfur nanocomposite material of the present invention does not need to add additional conductive carbon and binder, nor does it need additional process steps such as ball milling, coating, and dry pressing. It can be directly stirred with the electrolyte to form a slurry, so that the electrolyte and the electroless metal / sulfur nanocomposite material can be evenly mixed, and the electrolyte can fully infiltrate the electroless metal / sulfur nanocomposite material. Therefore, the prepared slurry can be directly dripped on the current collector to form a cathode, and the cathode has good electronic conductivity through the metal plating layer, good ionic conductivity through electrolyte infiltration, and good dispersibility of the electroless metal / sulfur nanocomposite material. Therefore, the cathode can achieve a high active material weight ratio (high sulfur content) while increasing the metal content of the electroless metal / sulfur nanocomposite material to highlight its performance advantages: the battery using it has high conductivity, high specific capacity, high energy density, and cycle stability.
[0048] The cathode of the present invention is made by drip coating, and no conductive carbon and binder are required to be added, so the problem of excess material absorbing part of the electrolyte can be overcome. Therefore, high electrolyte abuse can be avoided, and the battery can use a small amount of electrolyte, so that high specific capacity and high energy density performance and excellent battery stability can be achieved.
[0049] The non-electroplated metal / sulfur nanocomposite material of the present invention can make the cathode using the same have a high metal content (5-40wt%) and a high sulfur content (60-95wt%), and can be operated in a oligoelectrolyte battery, so it can achieve stable cycling of up to 200 cycles under slow C / 20 (long time), average C / 10, and high C / 5-C / 2 (high power) conditions, and achieve the performance of high specific capacity and high energy density.
[0050] The electroless metal / sulfur cathode of the present invention utilizes an electroless metal / sulfur nanocomposite material with a metal shell layer to enhance the cathode conductivity, thereby improving the problem of slow reaction of a small amount of electrolyte and the poor reactivity of lithium sulfide, and obtaining high reaction kinetics. Therefore, the weight ratio of electrolyte to sulfur is effectively reduced, the true electrochemical reaction characteristics of the sulfur cathode can be displayed, and the battery can also achieve the advantages of high energy density and high cycle stability.
[0051] The battery of the present invention has a high area specific discharge capacity (7-14 mA·h / cm 2 ) and high energy density (13~28mW·h / cm 2 ) performance, and can achieve a long cycle period of up to 200 cycles in a wide range of cycle rates (C / 20~C / 2), which has technical development potential and commercial value.
Brief Description of the Drawings
[0052] [ Figure 1](a) Figure shows the process of preparing electroless nickel / sulfur nanocomposites and the drip coating method; (b) microstructure and elemental analysis (SEM image) of sulfur powder and (c) electroless nickel / sulfur nanocomposites; (d) nitrogen adsorption-desorption isotherms of electroless nickel / sulfur nanocomposites (light color) and sulfur powder (dark color); (e) porosity analysis of electroless nickel / sulfur nanocomposites (dark color) and sulfur powder (light color); microstructure and elemental analysis (SEM image) of electroless nickel / sulfur cathode before (f) and after (g) 200 cycles.
[0053] [ Figure 2 ] are digital images and magnetic test diagrams of (a), (c) sulfur powder and (b), (d) electroless nickel / sulfur nanocomposites.
[0054] [ Figure 3 ] are X-ray energy dispersion spectra of (a) sulfur powder and (b) electroless nickel / sulfur nanocomposite materials.
[0055] [ Figure 4 ] are the X-ray diffraction spectra of sulfur powder (dark color) and electroless nickel / sulfur nanocomposite material (light color).
[0056] [ Figure 5 ] is a graph of pore size distribution analysis of electroless nickel / sulfur nanocomposite materials (dark color) and sulfur powder (light color) using (a) BJH method (Barrett-Joyner-Halenda method), (b) density functional theory method, and (c) HK method (Horvath-Kawazoe method).
[0057] [ Figure 6 ] are (a) Nyquist plots of electroless nickel / sulfur nanocomposite materials (dark color) and sulfur powder (light color); (b) to (c) Bode plots; CV curves of electroless nickel / sulfur cathode subjected to 10 repeated qualitative scans in CV at a scanning rate of (d) 0.020 mV / s (e) 0.025 mV / s (f) 0.030 mV / s (g) 0.035 mV / s (h) 0.040 mV / s; (i) rate-dependent CV curves.
[0058] [ Figure 7 ] is a graph of lithium ion diffusion coefficients for an electroless nickel / sulfur cathode.
[0059] [ Figure 8 ] are (a) cycle capacity diagrams of batteries using electroless nickel / sulfur cathodes tested at cycle rates of C / 20, C / 10, C / 5, C / 3, and C / 2 for 200 cycles; and (b) charge and discharge voltage curves for 200 cycles at cycle rates of (c) C / 20, (d) C / 5, (e) C / 3, and (f) C / 2.
[0060] [ Fig. 9 ] is a graph of the area ratio discharge capacity of the electroless nickel / sulfur cathode at cycle rates of C / 20, C / 10, C / 5, C / 3, and C / 2 (4.0 mAh / cm in the figure). 2 The area required for electric vehicle batteries is ratio to discharge capacity).
[0061] [ Fig.10 ] is a graph of the weight-to-weight ratio discharge capacity of the electroless nickel / sulfur cathode at cycle rates of C / 20, C / 10, C / 5, C / 3, and C / 2, respectively.
[0062] [ Fig.11 ] are graphs of (a) upper platform discharge capacity and (b) lower platform discharge capacity of the electroless nickel / sulfur cathode at cycle rates of C / 20, C / 10, C / 5, C / 3, and C / 2, respectively.
[0063] [ Fig.12 ] are polarization analysis diagrams of electroless nickel / sulfur cathode at cycle rates of C / 20, C / 10, C / 5, C / 3, and C / 2, respectively.
[0064] [ Fig.13 ] is a graph showing the electrochemical characteristics of a pure sulfur cathode at a C / 20 cycle rate.
[0065] [ Fig.14 ] are pictures showing the morphology, microstructure and elemental analysis results of the electroless nickel / sulfur cathode before cycling ((a) to (b) are low magnifications, (c) to (d) are high magnifications).
[0066] [ Fig.15 ] are pictures showing the morphology, microstructure and elemental analysis results of the electroless nickel / sulfur cathode after the battery was cycled 200 times at a C / 20 cycle rate ((a) to (b) are low rates, (c) to (d) are high rates).
[0067] [ Fig.16 ] are pictures showing the morphology, microstructure and elemental analysis results of the electroless nickel / sulfur cathode after the battery was cycled 200 times at a C / 10 cycle rate ((a) to (b) are low rates, (c) to (d) are high rates).
[0068] [ Fig.17 ] are pictures showing the morphology, microstructure and elemental analysis results of the electroless nickel / sulfur cathode after the battery was cycled 200 times at a C / 5 cycle rate ((a) to (b) are low rates, (c) to (d) are high rates).
[0069] [ Fig.18] are figures showing the morphology, microstructure and elemental analysis results of the electroless nickel / sulfur cathode after the battery was cycled 200 times at a C / 3 cycle rate ((a) to (b) are low rates, (c) to (d) are high rates).
[0070] [ Fig.19 ] are figures showing the morphology, microstructure and elemental analysis results of the electroless nickel / sulfur cathode after the battery was cycled 200 times at a C / 2 cycle rate ((a) to (b) are low rates, (c) to (d) are high rates).
[0071] [ Fig. 20 ] are the XRD synthesis phase data and component analysis data diagrams of the electroless nickel / sulfur nanocomposite materials synthesized by 0.1M nickel chloride plating solution at (a) 70°C, (b) 80°C, (c) 90°C, and 0.25M nickel chloride plating solution at (d) 70°C, (e) 80°C, (f) 90°C.
[0072] [ Fig.21 ] are thermogravimetric analysis data graphs of electroless nickel / sulfur nanocomposites synthesized by 0.1M nickel chloride plating solution at (a) 70°C, (b) 80°C, (c) 90°C, and 0.25M nickel chloride plating solution at (d) 70°C, (e) 80°C, (f) 90°C.
[0073] [ Fig. 22 ] are the results of the battery under different sulfur contents of 60wt%, 75wt%, 85wt%, 95wt%, and 100wt% (reference) and different sulfur loadings (a) 2mg / cm 2 (b) 6 mg / cm 2 Performance test diagram under the condition of . [Implementation Method]
[0074] The following examples illustrate the method for preparing the electroless metal / sulfur nanocomposite material, the electroless metal / sulfur cathode using the nanocomposite material, and the performance of a battery using the cathode. It should be noted that the following examples are only used to illustrate the present invention, and are not used to limit the scope of the present invention.
[0075] Example 1
[0076] [Preparation of electroless nickel / sulfur nanocomposites]
[0077] The preparation of electroless nickel / sulfur nanocomposites begins with material sensitization. The sensitizing solution is prepared as follows: 4 mL of hydrochloric acid is diluted into 100 mL of deionized water, and after being evenly mixed, 1 g of stannous chloride (SnCl2) is added and stirred with a magnet. Commercially pure sulfur powder is poured into the sensitizing solution and stirred evenly for 1 hour. Many easily oxidized Sn are adsorbed on the surface of the sulfur particles. 2+ions and then filtered to obtain the sensitized powder, which was then poured into the activation solution.
[0078] The activation solution is prepared as follows: 0.25 mL of hydrochloric acid is diluted to 100 mL of deionized water, and after uniform mixing, 0.025 g of palladium chloride (PdCl2) is added and uniformly mixed. The sensitized powder obtained by filtration is added to the activation solution, stirred uniformly for 1 hour, and then filtered and rinsed with deionized water to form a highly active network on the surface of the sulfur particles as a pretreatment powder.
[0079] Next, the acid chemical plating steps are as follows: Watts bath electroplating solution is made of 5g sodium acetate (NaAc) and 3g nickel chloride (NiCl2) dissolved in 50mL deionized water, and 1g sodium hypophosphite (NaH2PO2·H2O) dissolved in 50mL deionized water. The above two solutions are preheated to 80°C and then combined and activated pre-treated powder is added. Then a glass rod is used to stir evenly for 1 hour. The sulfur activated surface will adsorb nickel ions in the solution. With the help of sodium hypophosphite reducing agent and high temperature, nickel ions undergo self-oxidation-reduction reaction and react into metal nickel atoms. The reaction rate of nickel salts and reducing agents is greatly affected by the concentration and temperature of the reducing agent. The higher the concentration of the reducing agent, the stronger its reducing ability and the faster the reaction rate. After the reaction is roughly completed, the surface is filtered and rinsed with deionized water for 3 times and the composite powder is taken out by suction, and it is placed in a 50°C convection oven for drying and grinding to form a non-electroplated nickel / sulfur nanocomposite material. The sulfur content of the nanocomposite material is 74wt%.
[0080] [Preparation of electroless nickel / sulfur cathode]
[0081] The electroless nickel / sulfur cathode is made by a drop coating method, where the electroless nickel / sulfur nanocomposite material is dissolved in an appropriate amount of electrolyte to form a slurry containing the electroless nickel / sulfur nanocomposite material and the electrolyte and drop coated on the current collector, and the weight ratio of the electrolyte to sulfur is 7 μL / mg (abbreviated as E / S). The aforementioned electrolyte is a mixture of 1.85M lithium bistrifluoromethanesulfonyl imide (referred to as LiTFSI), 0.2M LiNO3 and a 55:40 volume ratio of ethylene glycol dimethyl ether / 1,3-dioxolane solution (referred to as DME / DOL solution), that is, 50.5mg LiTFSI and 1.3mg LiNO3 are co-dissolved in 55mL DME and 40mL DOL.
[0082] [Battery preparation]
[0083] The battery is assembled in the order of the cathode, separator, and lithium anode. Each component is sealed into a CR2032 button-type battery in a glove box under an argon atmosphere. The sulfur loading of the cathode is 14 mg / cm 2 .
[0084] Example 2
[0085] [Preparation of electroless nickel / sulfur nanocomposites]
[0086] The preparation of sulfur-nickel nanocomposites begins with material sensitization. The sensitizing solution is prepared as follows: 0.4 mL of hydrochloric acid is diluted into 10 mL of deionized water, and after being evenly mixed, 0.1 g of stannous chloride (SnCl2) is added and stirred with a magnet. Commercially pure sulfur powder is poured into the sensitizing solution and stirred evenly for 1 hour. Many easily oxidized Sn are adsorbed on the surface of the sulfur particles. 2+ ions and then filtered to obtain the sensitized powder, which was then poured into the activation solution.
[0087] The activation solution is prepared as follows: 0.025 mL of hydrochloric acid is diluted to 10 mL of deionized water, and after being evenly mixed, 0.0025 g of palladium chloride (PdCl2) is added and evenly mixed to prepare the solution. The sensitized powder obtained by filtration is added to the activation solution, stirred evenly for 1 hour, and then filtered and rinsed with deionized water to form a highly active network on the surface of the sulfur particles as a pretreatment powder.
[0088] Next, the acid chemical plating steps are as follows: a Watts bath electroplating solution is prepared by dissolving sodium acetate (NaAc) and nickel chloride (NiCl2) in 5 mL of deionized water to prepare a 0.1 M nickel chloride plating solution. In addition, sodium hypophosphite (NaH2PO2·H2O) is dissolved in 5 mL of deionized water. The grams of sodium hypophosphite and nickel chloride powders are determined based on the ion ratio (Ni 2+ ·H2PO2 2- ) is 0.5 as the benchmark, the two solutions are preheated to 70°C and then combined and the activated pre-treated powder is added, and then a glass rod is used to stir evenly for 1 hour. The sulfur activated surface will adsorb the nickel ions in the solution. With the help of sodium hypophosphite reducing agent and high temperature, the nickel ions undergo self-oxidation-reduction reaction and react into metal nickel atoms. The reaction rate of nickel salts and reducing agents is greatly affected by the reducing agent concentration and temperature. The higher the reducing agent concentration, the stronger its reducing ability and the faster the reaction rate. After the reaction is roughly completed, the surface is filtered and rinsed with deionized water for 3 times, and the composite powder is taken out by suction, and placed in a 50°C convection oven for drying and grinding to form a non-electroplated nickel / sulfur nanocomposite material. The sulfur content of the nanocomposite material is 95wt%.
[0089] [Preparation of electroless nickel / sulfur cathode]
[0090] The electroless nickel / sulfur cathode is made by a drop coating method, where the electroless nickel / sulfur nanocomposite material is dissolved in an appropriate amount of electrolyte to form a slurry containing the electroless nickel / sulfur nanocomposite material and the electrolyte and drop coated on the current collector, where the weight ratio of the electrolyte to sulfur is 20 μL / mg. The aforementioned electrolyte is a mixture of 1.85M LiTFSI, 0.2M LiNO3 and a DME / DOL solution with a volume ratio of 55:40, that is, 50.5mgLiTFSI and 1.3mgLiNO3 are co-dissolved in 55mL DME and 40mL DOL.
[0091] [Battery preparation]
[0092] The battery was assembled in the order of the cathode, separator, and lithium anode. Each component was sealed into a CR2032 button-type battery in a glove box under an argon atmosphere. The sulfur loading of the cathode was 2 mg / cm 2 .
[0093] Example 3
[0094] The electroless nickel / sulfur nanocomposite material, the electroless nickel / sulfur cathode and the battery were prepared as described in Example 2 except that the concentration of the nickel chloride plating solution in Example 2 [Preparation of electroless nickel / sulfur nanocomposite material] was changed to 0.25 M.
[0095] Example 4
[0096] The electroless nickel / sulfur nanocomposite material, the electroless nickel / sulfur cathode and the battery were prepared as described in Example 2, except that the two solutions in Example 2 [Preparation of electroless nickel / sulfur nanocomposite material] were preheated to 80°C and the sulfur content was changed to 85wt%.
[0097] Example 5
[0098] The electroless nickel / sulfur nanocomposite material, the electroless nickel / sulfur cathode and the battery were prepared as described in Example 2, except that the concentration of the nickel chloride plating solution in Example 2 [Preparation of electroless nickel / sulfur nanocomposite material] was changed to 0.25 M, the two solutions were preheated to 80° C., and the sulfur content was changed to 75 wt %.
[0099] Example 6
[0100] The electroless nickel / sulfur nanocomposite material, the electroless nickel / sulfur cathode and the battery were prepared as described in Example 2, except that the two solutions in Example 2 [Preparation of electroless nickel / sulfur nanocomposite material] were preheated to 90° C. and the sulfur content was changed to 75 wt %.
[0101] Example 7
[0102] The electroless nickel / sulfur nanocomposite material, the electroless nickel / sulfur cathode and the battery were prepared as described in Example 2, except that the concentration of the nickel chloride plating solution in Example 2 [Preparation of electroless nickel / sulfur nanocomposite material] was changed to 0.25 M, the two solutions were preheated to 90° C., and the sulfur content was changed to 60 wt %.
[0103] Embodiments 8 to 13
[0104] Examples 8 to 13 are respectively the following: the sulfur loading in the [battery preparation] of Examples 2 to 7 is changed to 6 mg / cm 2 , and the rest are the same as described in Examples 2 to 7 to prepare electroless nickel / sulfur nanocomposites, electroless nickel / sulfur cathodes and batteries.
[0105] Comparative Examples 1 to 6
[0106] [Preparation of pure sulfur powder cathode]
[0107] 75 mg of pure sulfur powder was mixed with 25 mg of SuperP conductive carbon black, and the mixed powder was placed in a 50°C convection oven to prepare 75 wt% pure sulfur powder containing 25 wt% conductive carbon. The 75 wt% pure sulfur powder cathode was prepared by drip coating, where the aforementioned 75 wt% pure sulfur powder was dissolved in an appropriate amount of electrolyte and dripped onto the current collector, with the electrolyte to sulfur weight ratio being 7 μL / mg. The above steps were repeated to prepare 75 wt% pure sulfur powder cathodes of Comparative Examples 1 to 6 under the same conditions.
[0108] [Battery preparation]
[0109] The battery is assembled in the order of the aforementioned 75wt% pure sulfur powder cathode, separator, electrolyte and lithium anode. In a glove box under an argon atmosphere, each component is sealed into a CR2032 button-type battery. The aforementioned electrolyte is a mixture of 1.85M LiTFSI, 0.2M LiNO3 and a DME / DOL solution with a volume ratio of 55:40, that is, 50.5mg LiTFSI and 1.3mg LiNO3 are co-dissolved in 55mL DME and 40mL DOL.
[0110] The electroless nickel / sulfur nanocomposite material, electroless nickel / sulfur cathode and battery prepared in Example 1 are further described and analyzed below.
[0111] [Electroless Nickel / Sulfur Nanocomposite Materials]
[0112] Figure 1 (a) is a method for synthesizing an electroless nickel / sulfur nanocomposite material, wherein sulfur powder (sulfur particles) is used as a raw material substrate for nickel plating. In order to improve the uniformity of plating, the present invention uses SnCl2 and PbCl2 as a sensitizer and an activator, respectively, to generate active sites on the sulfur particles. The sensitization step allows the surface of the sulfur particles to adsorb easily oxidized Sn.2+ ions, and then in the activation step Sn 2+ The ions are oxidized and an activation layer is formed on the surface of the sulfur particles as a crystallization nucleus, which can accelerate the reduction reaction of nickel ions and promote the uniform deposition of nickel. Electroless nickel plating is an autocatalytic reaction, in which the nickel ions in the nickel salt undergo a reduction reaction on the surface of the reducing agent:
[0113] The sensitization and activation time of Example 1 is 1 hour. Such a time setting is for uniform pretreatment of the self-oxidation-reduction reaction sites on the surface of the sulfur powder, which is conducive to the formation of a homogeneous surface coating, so that the electroless nickel / sulfur nanocomposite material can have a high nickel content.
[0114] Electroless nickel plating uses nickel salt and strong reducing agent to react and deposit metal nickel ions on the surface of sulfur powder. Figure 2 As shown, the color of the obtained electroless nickel / sulfur nanocomposite material changes from yellow to yellow-gray before and after the deposition reaction, and it has magnetic properties. The change in its physical properties shows that the electroless nickel / sulfur nanocomposite material is a nickel coating formed on a nanocomposite material based on sulfur powder.
[0115] Scanning electron microscopy (SEM) was used to compare the microstructure and elemental composition of pure sulfur powder and electroless nickel-sulfur nanocomposites. Figure 1 (b) Figure 1 As shown in (c), the sulfur particles of pure sulfur powder have a rough surface and a particle size of 10 to 20 μm. In contrast, the electroless nickel / sulfur nanocomposite material is characterized by a thin nickel layer uniformly coated on the sulfur particles, and its particle size is almost the same as that of pure sulfur powder. Further elemental analysis showed that the chemical composition of the electroless nickel / sulfur nanocomposite material is 74 wt% sulfur, 24 wt% nickel, and 2 wt% phosphorus (impurity).
[0116] Figure 3 , Figure 4 The X-ray energy dispersive spectra (EDS) and X-ray diffraction spectra (XRD patterns) of pure sulfur powder and electroless nickel / sulfur nanocomposites are shown. They also confirmed the presence of nickel plating. The four-point resistivity system was used for measurement, and the results showed that the conductivity of the electroless nickel / sulfur nanocomposites increased from pure insulation to 0.03S / cm, and its surface area and pore size distribution were shown in Figure 1 (d) Figure 1 (e) Nitrogen adsorption-desorption isotherms show that the material has similar surface adsorption-desorption behaviors before and after the formation of electroless nickel. Figure 5 The results of the pore size analysis show that the surface area of the material before and after the electroless nickel plating is low (less than 10m 2 / g) and a total pore volume of 0.01 cm 3 / g, indicating that both materials are non-nanoporous (surface area less than 10m 2 / g is defined as a material without nanopores), and the detailed physical and chemical properties are shown in Table 1. These properties show that the electroless nickel plating reaction is only to add a nickel nanoshell layer (nickel plating layer) to the sulfur particles, and there is no obvious composition or structural change in the sulfur powder particle substrate.
[0117] [Table 1]
[0118]
[0119] Metallic nickel has a high conductivity of more than 0.1 S / cm. The present invention applies nickel to the sulfur cathode to improve the chemical properties of lithium-sulfur batteries: reduce cathode resistance, retain polysulfides, and promote the redox reaction of solid sulfur active substances. Methods for making electroless nickel / sulfur cathodes, such as Figure 1 As shown in (a), the electroless nickel / sulfur nanocomposite material is dispersed in a liquid electrolyte to form a slurry, and then the slurry containing the electroless nickel / sulfur nanocomposite material and the electrolyte is dripped onto the current collector. The electroless nickel / sulfur nanocomposite material of the present invention does not need to add additional conductive carbon and binder, nor does it need additional process steps such as ball milling, coating, and dry pressing. It is directly stirred with the electrolyte to form a slurry. This step can ensure the uniform mixing of the electrolyte and the electroless nickel / sulfur nanocomposite material, and the electrolyte fully infiltrates the electroless nickel / sulfur nanocomposite material. Therefore, the prepared slurry can be directly dripped onto the current collector to form a cathode. The cathode has good electronic conductivity by means of the metal nickel plating layer, good ionic conductivity by means of electrolyte infiltration, and good dispersibility of the electroless nickel / sulfur nanocomposite material. Therefore, the cathode can achieve a high active material weight ratio (high sulfur content) while increasing the nickel content of the electroless nickel / sulfur nanocomposite material to highlight its performance advantages: the battery has a high specific capacity, high energy density, and cycle stability.
[0120] like Figure 1 (f)~ Figure 1 As shown in (g), the elemental analysis results show that the electroless nickel / sulfur cathode has a significant nickel coating tightly attached to the sulfur particles. According to Table 1 above, the nickel coating improves the conductivity of the electroless nickel / sulfur nanocomposite and forms a long-range electron transport network, thereby reducing the cathode impedance. In addition, the conductive network can be evenly applied to each sulfur particle to capture and electrocatalyze the polysulfides generated during the battery cycle. Therefore, Figure 1As shown in (g), the electroless nickel / sulfur cathode after battery cycling reaction still shows a strong sulfur element signal in the solid sulfur-based active material even when directly exposed to the liquid electrolyte, confirming the enhanced retention of polysulfides and reduced loss of active materials. The surface of the electroless nickel / sulfur nanocomposite after battery cycling reaction has muddy precipitation, which is due to the conversion of captured polysulfides into stable sulfur materials. The muddy sediment is mainly concentrated on the electrocatalytic nickel points, forming small particles rather than huge agglomerates, indicating that it still has high electrochemical activity.
[0121] [Electrochemical characteristics of electroless nickel / sulfur cathode and battery]
[0122] Figure 6 To measure the electrochemical characteristics of electroless nickel / sulfur cathodes and batteries. Figure 6 As shown in (a) to (c), the resistance and reaction kinetics of the battery were analyzed by electrochemical impedance spectroscopy (EIS). The Nyquist plots of the electroless nickel / sulfur cathode and the sulfur reference cathode show that the bulk resistance in the real part of the impedance is as low as 7 and 13 ohms, respectively. The semicircle generated by the charge transfer impedance indicates that the nickel plating reduces the charge transfer resistance from 210 ohms to 52 ohms, which will be beneficial to the reaction capacity of the electroless nickel / sulfur cathode, enabling it to achieve higher electrochemical utilization and rate capability. The inclined line in the low-frequency region represents the Warburg impedance, which shows that the electroless nickel / sulfur cathode presents a lower diffusion impedance. The Bode plot once again confirms the main enhancement role of the electroless nickel / sulfur nanocomposite in reducing the charge transfer resistance and diffusion impedance.
[0123] according to Figure 6 As shown in (d) to (h), the redox reaction of the electroless nickel / sulfur cathode was analyzed by cyclic voltammetry (CV). Figure 6 In (d), the reversible CV scan curve at 0.020 mV / s describes the stable redox reaction between sulfur and lithium sulfide during the lithiation / delithiation process. In the 3.0V to 1.5V range of the CV scan, the two-step reduction reaction of sulfur includes two obvious cathode peaks (cathode peak 1 and cathode peak 2), cathode peak 1 and cathode peak 2 represent the reduction reaction of solid sulfur to liquid polysulfide and solid sulfide, respectively. From 1.5 to 3.0V, the two-step oxidation reaction shows a broader anodic peak, corresponding to the oxidation reaction from sulfide to polysulfide and sulfur. The CV curve did not show obvious changes in potential and current density during 10 consecutive scans, indicating stable low polarization and reversible electrochemical reactions, respectively. And, as Figure 6As shown in (d) to (h), when the scan rate increases from 0.020 mV / s to 0.040 mV / s, the cathode and anode reactions only show a slight increase in polarization, and no significant changes in potential and current density are shown during 10 consecutive scans, showing the same excellent electrochemical reversibility and stability, showing excellent rate capability. Figure 6 As shown in (i), the rate-dependent CV scan is collected based on the second CV curve from a scan rate of 0.020 to 0.040 mV / s to calculate the lithium ion diffusion coefficient by the relationship between the peak current and the CV scan rate.
[0124] like Figure 7 As shown in the figure, the calculated lithium ion diffusion coefficients of cathode peak 1, cathode peak 2 and anode peak are 4.16×10 -8 4.44×10 -7 and 1.57×10 -7 cm 2 / s. The high diffusion coefficient shows the stable diffusion ability of lithium ions in the electroless nickel / sulfur cathode and its high electrochemical utilization. According to EIS and CV analysis, the smooth migration of electrons and ions in the electroless nickel / sulfur nanocomposite ensures its ability to serve as a high-performance cathode, and the cathode can achieve high sulfur weight and normal battery cycling in oligoelectrolyte batteries.
[0125] [Battery performance using electroless nickel / sulfur cathode]
[0126] Figure 8 To explore the long-term cycle rate capability and discharge / charge voltage curve of the lithium-sulfur battery of Example 1. Figure 8 As shown in (a), the battery has a high area specific discharge capacity of 1,008, 901, 674, 550, and 460 mA·h / g at wide cycle rates of C / 20, C / 10, C / 5, C / 3, and C / 2, respectively. After 200 cycles, the reversible capacity of the battery shows a good capacity retention rate (50-70%), and the capacity decay rate is as low as 0.05% per cycle. The coulombic efficiency of the battery is still maintained as high as 98-99%.
[0127] The battery can reach 200 cycles at different cycle rates of C / 20, C / 10, C / 5, C / 3, and C / 2, and retain 48%, 51%, 67%, 70%, and 64% of the capacity. Calculating the ratio of the discharge capacity after 100 cycles to the second discharge capacity, the retention rate is 76%, 81%, 94%, 94%, and 95%. Detailed information is summarized in Table 2 below.
[0128] [Table 2]
[0129]
[0130] In summary, it is shown that the applied electroless nickel / sulfur nanocomposite has excellent rate capability, electrochemical stability and efficiency.
[0131] like Fig. 9 As shown, the battery using the electroless nickel / sulfur cathode shows 14 to 7 mA·h / cm at various cycle rates from C / 20 (slow) to C / 2 (fast). 2 The high area ratio discharge capacity and the corresponding energy density value are close to 28-13mW·h / cm 2 In comparison, the performance of commercial lithium-ion battery cathodes is 2 to 4 mA·h / cm 2 and 10~14mW·h / cm 2 .
[0132] In addition, if Fig.10 As shown, due to the high sulfur content of the cathode, the battery performance can reach a high capacity of 744 mA·h / g based on the total weight of the cathode. In summary, the battery using the electroless nickel / sulfur cathode exhibits excellent electrochemical characteristics and battery performance: high utilization, high capacity retention, and reaction kinetics, and the cathode can achieve high sulfur weight and increase the active material content in a small amount of electrolyte battery.
[0133] Figure 8 (b) to (f) show the discharge and charge voltage curves of the electroless nickel / sulfur cathode at different cycle rates to explore its redox conversion ability and stability. Figure 6 As shown, the charge / discharge curves almost overlap and correlate with the anode / cathode peaks in the CV curve, confirming a typical lithium-sulfur redox conversion. In addition, no irreversible capacity loss and other decomposition reactions of the metal plating were observed. From 3.0 to 1.5 V, the upper and lower discharge platforms overlap at different cycle rates, showing the excellent discharge reversibility and cyclability of the electroless nickel / sulfur cathode. Fig.11 As shown in Figure 2, the stable discharge capacities of the upper and lower discharge platforms of the electroless nickel / sulfur cathode show a complete conversion reaction and are consistent with Figure 8 The discharge curves in (b) to (f) are consistent. Fig.11 As shown in (a), at different rates, the discharge capacity of the upper platform shows similar trends, which is due to the rapid conversion reaction from sulfur to highly active polysulfides. The electrochemically active polysulfides are retained on the nickel coating and can act as cathode electrolytes, thereby limiting the loss of active materials and enhancing the redox conversion rate. At the same time, at different rates, the discharge capacity of the lower platform shows the challenge of high discharge rates for high-load cathodes. The slow liquid-solid conversion from highly active polysulfides to insulating sulfides has a more comprehensive reduction reaction at low rates compared to high rates. Fig.11As shown in (b), although the discharge capacity of the lower platform is affected by the cycle rate, the electroless nickel / sulfur cathode still has good cycling ability from low to high rates after 200 cycles, which is due to the high polysulfide capture and activation ability of the nickel coating. Figure 8 As shown, from 1.5 to 3.0 V, the overlapping charge platform shows that a large amount of sulfur produced in the discharge reaction is successfully oxidized. When the battery voltage approaches 3.0 V, the almost vertical voltage increase means that the battery using the electroless nickel / sulfur cathode can be fully charged, indicating that the high conductivity and electrocatalytic properties of the nickel plating can promote the oxidation reaction.
[0134] Next, based on the data from the discharge and charge platforms of the electroless nickel / sulfur cathode, the inherent polarization problem when using an electroless nickel / sulfur cathode with a high sulfur loading and a low electrolyte to sulfur weight ratio is discussed. Fig.12 As shown, the electroless nickel / sulfur cathode maintains low polarization at cycle rates of C / 20 to C / 3, and there is no increase in polarization after 200 cycles; at a cycle rate of C / 2, the polarization phenomenon increases because of the slow liquid-solid reduction reaction of the lower discharge platform, so it does not significantly affect the electrochemical reaction.
[0135] In contrast, Fig.13 The results show that the 75wt% pure sulfur powder cathode of Comparative Examples 1 to 6 is applied to the battery. As mentioned above, the ratio of electrolyte to sulfur weight of the batteries of Example 1 and Comparative Examples 1 to 6 is 7μL / mg, and the ratio of electrolyte to sulfur weight is 14mg / cm 2 Moreover, the sulfur content of the 75wt% pure sulfur powder cathode of Comparative Examples 1 to 6 is 75wt%, while the sulfur content of the electroless nickel / sulfur cathode of Example 1 is 74wt%, and the sulfur contents thereof are equivalent, so the 75wt% pure sulfur powder cathode and the electroless nickel / sulfur cathode are made under the same conditions.
[0136] according to Figure 8 (a) Fig.13 It can be found that the performance comparison of 75wt% pure sulfur powder cathode and electroless nickel / sulfur cathode is:
[0137] (A) The electroless nickel / sulfur cathode can be cycled up to 200 times at a battery cycle rate of C / 20 to C / 2, while the 75wt% pure sulfur powder cathode can only be cycled at a slow rate of C / 20 and cannot be cycled for more than 200 times (10 to 20 times), and the battery performance is extremely unstable;
[0138] (B) The electroless nickel / sulfur cathode can achieve a high Coulomb effect (over 95%) at different rates, while the 75wt% pure sulfur powder cathode has no stable Coulomb effect and the Coulomb effect value is difficult to reach over 90%;
[0139] (C) Under slow C / 20 cycling, the electroless nickel / sulfur cathode can reach a capacity of 1,008 mA·h / g, but the 75 wt % pure sulfur powder cathode can only reach a maximum capacity of 700 mA·h / g.
[0140] According to the above, the battery assembled with the 75wt% pure sulfur powder cathode of Comparative Examples 1 to 6 cannot be cycled normally and has a small discharge capacity because there is no nickel coating to provide a conductive network to improve the electrochemical utilization of the electrode. In addition, since there is no nickel coating, polysulfides can be retained in the cathode and used as a cathode electrolyte to activate unreacted sulfur, which in turn leads to unstable coulombic efficiency.
[0141] Figures 14 to 19 The morphology, microstructure and elemental analysis results of the electroless nickel / sulfur cathode before and after 200 cycles at C / 20 to C / 2 cycle rates. Figures 14 to 19 The six images in (b) and (d) from top to bottom and from left to right are the elemental analysis of five elements, sulfur (S), nickel (Ni), carbon (C), fluorine (F), and oxygen (O). As shown in the figure, the observation results of the electroless nickel / sulfur cathode at high and low rates show that it has almost the same cathode morphology before and after the cycle. In addition, its almost unchanged microstructure and elemental spectrum analysis results also confirm that the nickel plating can promote the activation and redox reaction of sulfur, and can stabilize polysulfides at the cathode as the cathode electrolyte. This result is also consistent with the electrochemical properties of the battery, confirming that the electroless nickel / sulfur nanocomposite material can promote the conductivity and electrocatalytic activity of the cathode, and can also prevent the formation of inactive deposits on the battery cathode during battery cycling.
[0142] In summary, the electroless nickel / sulfur nanocomposite material provides a new research direction for the development of lithium-sulfur batteries with sulfur cathodes having excellent performance. The electroless nickel / sulfur nanocomposite material of the present invention has been evenly mixed with the electrolyte, and no conductive carbon and binder need to be added, and good cathode functionality can be achieved by using a drip coating method. In addition, the nickel plating forms a thin and light nanocoating on the surface of the sulfur particles, which reduces insulation, enhances the electrochemical reaction kinetics through metal catalysis, and uses metal activity to perform physical and chemical adsorption of liquid polysulfides, demonstrating high electrochemical utilization and stable cyclic charge and discharge performance. Therefore, the electroless nickel / sulfur cathode prepared using the electroless nickel / sulfur nanocomposite material can achieve, for example, 14 mg / cm 2 The high sulfur loading and high sulfur content of 74 wt% can achieve a high sulfur weight of 7 μL / mg in a small amount of electrolyte battery, which is much better than the existing technology (low sulfur loading is only 2 mg / cm 2, low sulfur content of only 30-60 wt%, and excessively high electrolyte volume (more than 20 μL / mg). The battery performance of the present invention can reach a high capacity of, for example, 1,008 mA·h / g, 7-14 mA·h / cm 2 High specific capacitance and energy density up to 13-28mW·h / cm 2 , which is superior to the energy density of commercial oxide electrodes (about 10 mW·h / cm 2 ), and can maintain high capacity for 200 cycles under a wide range of charge and discharge rates from C / 20 to C / 2. Batteries using electroless nickel / sulfur cathodes exhibit excellent electrochemical properties and battery performance: high utilization, high capacity retention, and reaction kinetics, and the cathode can achieve high sulfur weight and increase active material content in oligo-electrolyte batteries.
[0143] The electroless nickel / sulfur nanocomposites prepared in Examples 2 to 7 are further described and analyzed below.
[0144] according to Fig. 20 , XRD synthesis phase data show that the electroless nickel / sulfur nanocomposite material of the present invention is mainly composed of pure sulfur powder, and component analysis data show that the nickel content of Examples 2 to 7 is 1.8wt%, 3.0wt%, 10.0wt%, 22.8wt%, 20.2wt%, and 34.2wt%, respectively; the sulfur content is 96.5wt%, 94.9wt%, 86.4wt%, 75.0wt%, 77.7wt%, and 60.2wt%, and the impurity components are 1.6wt%, 2.0wt%, 3.5wt%, 2.1wt%, 2.0wt%, and 5.5wt% (all lower than 5.5wt%). The results show that the long-term (60 minutes) high-temperature acidic chemical plating at 70 to 90°C of the present invention helps to reduce the generation of alloy impurities to only 1 to 5.5wt% or less, so a high nickel content can be achieved.
[0145] according to Fig.21 The thermal analysis data show that the electroless nickel / sulfur nanocomposites of Examples 2 to 7 contain 60 to 95 wt % sulfur content, which is consistent with the XRD synthetic phase data results, and its generation is only 1 to 5.5 wt % or less, so a high nickel content can be achieved.
[0146] The batteries prepared in Examples 2 to 13 are further described and analyzed below.
[0147] like Fig. 22 As shown, the battery has different sulfur contents of 60wt%, 75wt%, 85wt%, 95wt%, and 100wt% (reference) at different sulfur loadings of 2mg / cm 2 , 6mg / cm 2The electrical performance tests were carried out under the following conditions, and the results showed that they could all achieve long cycles.
[0148] The electroless nickel / sulfur nanocomposite material, electroless nickel / sulfur cathode and battery of the present invention are further analyzed and summarized below.
[0149] The electroless nickel / sulfur nanocomposite material of the present invention can achieve a high nickel content (10-40 wt%) in the battery cathode while maintaining a high sulfur content (60-95 wt%), which can improve the electrochemical properties compared with the prior art, and has a high specific capacity and energy density of 7-14 mA·h / cm 2 and 13~28mW·h / cm 2 , which is much better than the 2-4 mA·h / cm2 of current lithium-ion battery technology. 2 Specific capacitance and 10~14mW·h / cm 2 Energy density.
[0150] [Testing Instrument]
[0151] The instruments and measuring methods used in the present invention are described in detail below:
[0152] The morphology, microstructure, and elemental analysis were performed using a scanning electron microscope (SEM, SU-1510, Hitachi) and an energy dispersive X-ray spectrometer (EDS, XFlash, Bruker) to collect elemental mapping signals and analyze them.
[0153] The resistivity and sheet resistance of the electrode materials were measured using a four-point resistivity system (Pro-4, Lucas).
[0154] The structure and porosity were analyzed at 77 K using an automatic gas adsorption analyzer (AutoSorb iQ, Anton Paar). The surface area was calculated using Brunauer-Emmett-Teller according to the nitrogen adsorption-desorption isotherms, and the pore characteristics were studied using the BJH method, the HK method, the density functional theory, and the T-plot method. Impedance spectroscopy was performed using a research-grade potentiostat / galvanostat (SP-150, Biologic) in the frequency range of 1 MHz to 100 MHz with an AC voltage amplitude of 5 mV.
[0155] Cyclic voltammetry and lithium ion diffusion analysis were performed using a research-grade potentiostat / galvanostat (SP-150, Biologic) at scan rates of 0.020, 0.025, 0.030, 0.035, and 0.040 mV / s in the scan voltage range of 1.5 to 3.0 V. Voltage curves, battery cycling performance, and polarization states were obtained using a programmable battery cycler (BCS-800 series, Biologic) at rates of C / 20, C / 10, C / 5, C / 3, and C / 2 in a voltage window of 1.5 to 3.0 V.
Claims
1. A method for making a non-electroplated metal / sulfur cathode, wherein the non-electroplated metal / sulfur cathode is made by a drip coating method, characterized in that The production steps include: The electroless metal / sulfur nanocomposite is dissolved in an electrolyte and then drop-coated on a current collector to form an electroless metal / sulfur cathode; wherein the non-electroplated metal / sulfur cathode does not contain conductive carbon and binder; Wherein, the weight ratio of the electrolyte to sulfur is 7 to 20 μL / mg; The synthesis steps of the electroless metal / sulfur nanocomposite material include: A. Sensitization step: adding stannous chloride to hydrochloric acid to prepare a sensitizing solution, adding sulfur powder to the sensitizing solution, stirring evenly, and filtering to obtain a sensitizing powder; B. Activation step: adding palladium chloride to hydrochloric acid to prepare an activation solution, adding the sensitized powder to the activation solution, stirring evenly, and filtering to obtain a pretreated powder; C. Acidic chemical plating step: dissolving sodium acetate and metal salts in deionized water to prepare solution 1 containing metal ions; dissolving sodium hypophosphite in deionized water to prepare solution 2; The solution 1 and the solution 2 are preheated to the same temperature and then mixed, and the pretreated powder is added and stirred evenly. After the metal ions are reduced to metal atoms, the obtained mixture is filtered, dried, and ground to prepare a non-electroplated metal / sulfur nanocomposite material.
2. The method according to claim 1, wherein: The metal salt is at least one selected from the group consisting of gold chloride, silver chloride, copper chloride, tin chloride, nickel chloride, cobalt chloride, and ferric chloride.
3. The method according to claim 1, wherein: The stirring time of the sensitization step is 10 to 180 minutes, the stirring time of the activation step is 10 to 180 minutes, and the stirring time of the acid chemical plating step is 10 to 180 minutes.
4. The method according to claim 1, wherein: The same temperature is 70-90°C.
5. The method according to claim 1, wherein: The sulfur content of the electroless metal / sulfur nanocomposite material is 60-95 wt %.
6. The method according to claim 1, wherein: The metal content of the electroless metal / sulfur nanocomposite material is 5-40 wt %.
7. An electroless metal / sulfur cathode, characterized in that: The method according to any one of claims 1 to 6 is used for preparation.
8. The electroless metal / sulfur cathode of claim 7, wherein: Its sulfur loading is 2~14mg / cm 2 .
9. A battery, characterized in that: Use of an electroless metal / sulphur cathode as claimed in claim 7 or 8.
Citation Information
Patent Citations
Preparation method and application of metal shell layer-coated surface composite positive electrode material
CN108063257A
Positive pole piece for lithium-sulfur batteries and preparation method thereof
CN103035879A